Research Trends of EFL Students in English Education Program: A 2005-2015 Survey - Iftanti, Erna; Shofiya, Arina (Dinamika Ilmu: Jurnal Pendidikan, 2017)
One of the purposes of English Education Program of State Islamic Institute of Tulungagung, Indonesia, is to lead the graduates to do research on linguistics and language teaching and to write a thesis accordingly. However, the preliminary study shows that there is some repeatedly done research of the same topics, because the students commonly spend their time copying and pasting or modifying their seniors’ previous studies during writing the research proposals. If the advisors are not punctual in advising their advisees, it is possible to do some unintentional plagiarism which furthers block the contribution toward the body of knowledge in English language and education. Therefore, this article is intended to describe research trends of EFL students in English education. This descriptive study done through a questionnaire survey to 450 out of 849 students’ theses reveals that during the last eleven year, TEFL is the most popular research topic, because it is their mainstream topic. Still, they include other topics than TEFL which are mostly researched by using Descriptive (Qualitative). However, the students’ theses also indicate the development of implementing various research methods i.e. Quantitative, Classroom Action Research, and Research & Development. Moreover, although it is revealed that the research has already indicated the appropriateness of research objective with its title and research background, the EFL students’ theses need some improvement on writing research gap, reviewing related literature and previous studies, and on drawing conclusion and stating suggestion and research contribution as well. This study is then useful as the basis to make a research road map and important to avoid plagiarism and set a thorough research contribution to the body of knowledge on TEFL in Indonesia.